PERMOHONAN ISBAT NIKAH BERDASARKAN KLASTERISASI PERNIKAHAN DI BAWAH TANGAN DI PENGADILAN AGAMA PALANGKA RAYA - Purnawati, Yeni; Syaiku, Syaikhu (Sharia Faculty of State Islamic Institute (IAIN) Palangka Raya, 2023)
This research is based on the increase in applications for Isbat Nikah in the last 3 years, in 2020 there were 66 applicants, 2021 there were 88 applicants, and in 2022 there were 176 applicants. Due to the continuous increase, moreover, because of many applicants who perform this underhand marriage located in the city or